2020
DOI: 10.17081/innosa.87
|View full text |Cite
|
Sign up to set email alerts
|

Salivary pH as an improvement parameter in patients with periodontitis: A pilot study

Abstract: Background: The pH is a chemical parameter of saliva widely studied at present, its normal range is between 6.5 and 7.2. Its alteration has been linked to different oral pathologies, such as periodontal diseases. The purpose of this study was to identify the usefulness of salivary pH measurement as an indicator of improvement in patients with periodontitis and to estimate its possible relationship with the biofilm index and the number of periodontal pockets. Methods: A descriptive-comparative pilot study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Initially, there were no significant differences in the mean pH levels in the TW and TWF groups (7.07 ± 0.32 and 6.99 ± 0.39, respectively). These results in subjects with gingivitis are in agreement with the findings of Orosco et al In their study, the mean initial salivary pH in the gingivitis group was 7.01 ± 0.25 [ 66 ]. In the studies by Garcia et al [ 67 ] and Koppolu et al [ 8 ], salivary pH levels in patients with gingivitis were slightly higher (7.3 and 7.21 ± 0.11, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…Initially, there were no significant differences in the mean pH levels in the TW and TWF groups (7.07 ± 0.32 and 6.99 ± 0.39, respectively). These results in subjects with gingivitis are in agreement with the findings of Orosco et al In their study, the mean initial salivary pH in the gingivitis group was 7.01 ± 0.25 [ 66 ]. In the studies by Garcia et al [ 67 ] and Koppolu et al [ 8 ], salivary pH levels in patients with gingivitis were slightly higher (7.3 and 7.21 ± 0.11, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…Govindraj et al [ 19 ] assessed viscosity and salivary pH differences between working and nonworking men and women and evaluated the effect of stress on salivary pH and viscosity. They have concluded that stress exerts its influence on salivary pH, flow rate, and viscosity.…”
Section: Discussionmentioning
confidence: 99%